Chef Wan On-Line / Norhayati Shamsudin - Shamsudin, Norhayati (2000)
This thesis, Chef Wan On-Line, is a website that is specially developed for our famous Chef, Chef Wan. Despite his name and recipes, there are still many people out there who need more information about his life and activities in general. Tins homepage will provide the information of Chef Wan, his activity and also the forum for his fans to communicate directly with him.